Biodegradability of Nanoparticle Modified Fiber Reinforced Polyester Resin Nanocomposite - Chowdhury, M. N. K.; Beg, M. D. H.; Khan, Maksudur R. (Elsevier Ltd, 2013)
Copper nanoparticles (CuNPs) have been synthesized under chemical reduction and in aqueous medium where polyvinyl alcohol (PVA) played a role as a stabilizer. From Transmission electron microscopy (TEM) images analysis, calculated average size of the synthesized CuNPs was 3.5 nm. The synthesized CuNPs were loaded in the oil palm empty fruit bunch (EFB) natural fibers. Surface of the fibers were modified by cationic agent (CA). The existance of hydroxyl group in fibres exhibit negative charge and inhibit the PVA surrounded negatively charged on CuNPs. Several types of composites were developed using hand mixing process by varying the fiber types. The developed composites were formulated using untreated empty fruit bunch fibers (UF) and CuNPs loaded EFB fibers (NF) with commercially available unsaturated polyester resin (UPER). The UF, NF, UPER and nanocomposites were characterized by Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), x-ray diffactometer (XRD), differential scanning calorimetry (DSC), tensile strength test, etc. The results from biodegradation study showed that significant weight loss was not observed for virgin resin (VR) and VR-NF nanocomposite whereas, the VR-UF composite showed ca. 13.3% weight loss at 90 days, reflected to preferential degradation of the natural fibers.